Evaluation of fluorogenic aminonaphthalenesulfonamides and 6-hydrazinobenz[de]isoquinoline-1, 3-diones for the detection of bacteria. (February 2016) - Luo, Jia Lin; Jin, Terry; Váradi, Linda; Perry, John D.; Hibbs, David E.; Groundwater, Paul W.
Abstract: New fluorogenic enzyme substrates were synthesized by the coupling of aminonaphthalenesulfonamides or 6-hydrazinobenz[ de ]isoquinoline-1, 3-diones with β-alanine. The 6-hydrazinobenz[ de ]isoquinoline-1, 3-diones were also condensed with a range of aryl aldehydes to give the corresponding hydrazones. The photophysical properties of the synthesized amines and hydrazines and their amide, hydrazide and hydrazone derivatives, were examined and they were also incorporated into Columbia agar in order to determine their potential for the detection of pathogenic bacteria. Highlights: New fluorogenic enzyme substrates prepared by coupling of ANS or HBI with β-alanine. ANS fluorophores have bathochromic shift of ∼93 nm from precursors. Increased fluorescence intensity on localization of an HBI into bacteria. Potential secondary reaction products prepared from HBI and aldehydes.